1999
DOI: 10.1021/jp983313d
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Pyrene Excited States with Oxygen on the Surface of Porous Silica Gel and Similar Surfaces

Abstract: Oxygen quenching of the singlet state of pyrene adsorbed on amorphous silica gel is studied by pulsed laser and rapid spectrophotometric methods. The quenching rate constant depends on the pore size of the silica and the method and temperature used to remove adsorbed water and surface silanol groups. The two possible mechanisms for O 2 quenching of excited pyrene on an SiO 2 surface are quenching by direct collision encounter on the excited state (Eley-Rideal) and quenching by surface adsorbed oxygen (Langmuir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…In previous studies 22- 24 it was clearly shown that O 2 rapidly quenched excited states on several surfaces. The kinetics were shown to be heterogeneous in nature.…”
Section: O 2 Quenchingmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous studies 22- 24 it was clearly shown that O 2 rapidly quenched excited states on several surfaces. The kinetics were shown to be heterogeneous in nature.…”
Section: O 2 Quenchingmentioning
confidence: 88%
“…Arene singlet excited states were shown to quench efficiently, and at room temperature the decay consisted of a mixture of Eley-Rideal, ER, and Langmuir-Hinschelwood, LH, kinetics. 23, 24 The ER mechanism describes quenching by direct collision of O 2 with the excited arene. The LH mechanism describes quenching by O 2 adsorbed on the surface.…”
Section: O 2 Quenchingmentioning
confidence: 99%
“…Adsorption on high T a silica gel places pyrene in different less favorable locations on the surface, as indicated by the reduced adsorption efficiency and higher oxygen quenching efficiency. 19 On the high T a silica gel, pyrene resides closer to any active sites which can accept electrons after photoirradiation. The closer proximity to the surface active sites results in a faster return of the photoejected electron to the surface-bound cation, decreasing the cation lifetime and increasing the thermoluminescence yields.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the O 2 quenching rate constant for pyrene on TiO 2 -SiO 2 is 3.5 × 10 6 Torr Ϫ1 s Ϫ1 , and compares well with that measured previously for pyrene on silica alone. 19 The ready access of O 2 to pyrene militates against any shielding effects of TiO 2 .…”
Section: Co-adsorption Of Pyrenementioning
confidence: 99%
“…This is a Langmuir-Hinshelwood (LH, ref 17) mechanism, which is observed at room temperature with coadsorbed N,N′-dimethylanaline (DMA) 18 and at sample temperatures below 260 K with added oxygen. 14 The adsorption of pyrene on silica gel is relatively strong, and movement on the surface within the time of photoinduced reactions is limited. 13 For example, it has been shown previously 10c that the movement of coadsorbed ferrocene is responsible for the quenching of the pyrene triplet, indicating that pyrene moves slowly on the SiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%